The role of brand credibility and brand experience in post-consumption outcomes of hotel choice among Malaysian Muslim consumers / Nadzirah Rosli - Nadzirah , Rosli (2020)
This research investigates the importance of hotel attributes in examining Malaysian Muslim tourists' hotel choice. Based on the mean-end chain theory, it explores the relationship among nine constructs; hotel attributes, brand credibility, brand experience, brand attachment and post-consumption outcomes which consisted of satisfaction, revisit intention and word-of-mouth, as well as travel motivation and Islamic religiosity. A total of 474 valid and usable self-administered questionnaires were collected through purposive sampling technique. Partial Least Squares Structural Equation Modelling (PLS-SEM) approach was deployed to validate the research model and the research hypotheses. The result indicates that brand experience fully mediates the relationship between hotel attributes and brand attachment. Hotel attributes was found to influence brand credibility and brand experience. On the other hand, brand experience was found to influence brand attachment and brand credibility. Likewise, brand credibility was found to influence satisfaction and revisit intention. In addition, brand attachment was found to influence satisfaction, revisit intention, and word-of-mouth. The findings also found that travel motivation moderates the relationship between brand attachment and post-consumption outcomes (i.e. satisfaction, revisit intention and word-of-mouth). The result offers implications for hotelier and direction for future research.